PERANCANGAN DECISION SUPPORT SYSTEM PADA BIBIT SALAK BERBASIS SIMPLE ADDITTIVE WEIGHTING - Teri Mengkasrinal (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Computers have a system that has the ability to help people in solving problems, with their decision support systems can improve the quality of decision support system that will be created. For example, the bark berkualitas.Sistem seed selection to be made in the decision making is by using SAW (Simple Additive Weighting). These applications seek a weighted summation of the performance rating for each alternative on all attributes, and requires a decision matrix normalization process to a scale that can be compared with all the ratings of existing alternatives. The report will describe the decision support system in the process of selection of seeds with good quality bark. Application of the method of this SAW, obtained seeds of good quality bark and accurately. Keywords: Decision Support Systems, Seed Salak, SAW